2018
DOI: 10.1016/j.mod.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Roles of basal keratinocytes in actinotrichia formation

Abstract: The embryonic fins and the tip of adult fins of teleost fish are supported by rows of straight, unmineralized fibrils called actinotrichia. The proximal ends of the actinotrichia are bundled and the mineralized bones called lepidotrichia are made along them. Since malformation in actinotrichia causes wavy fin bones, the correct configuration of actinotrichia is essential for the correct construction of the fin shape. Past studies suggested that two types of cells, basal keratinocytes, and mesenchymal cells inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Prior to conducting the in vitro study, we established a new actinotrichia-visualized zebrafish line [5x and1 (2k): And1 full -GFP] to allow more detailed observation of the cell and actinotrichia dynamics ( Supplementary Figure 1 ). The fins of this new actinotrichia-visualized zebrafish showed even greater fluorescence intensity of the actinotrichia compared to the previously reported visualization line ( Kuroda et al, 2018 ) ( Supplementary Figures 1 , 2 ). Using previously reported methods ( Kuroda et al, 2018 ), we first isolated the actinotrichia and mesenchymal cells from the larval fins of our new transgenic F1 line [5x and1 (2k): And1 full -GFP/5x and1 (MC): Lifeact-mCherry] and cultured them in culture dishes coated with various kinds of substrates.…”
Section: Resultsmentioning
confidence: 39%
See 4 more Smart Citations
“…Prior to conducting the in vitro study, we established a new actinotrichia-visualized zebrafish line [5x and1 (2k): And1 full -GFP] to allow more detailed observation of the cell and actinotrichia dynamics ( Supplementary Figure 1 ). The fins of this new actinotrichia-visualized zebrafish showed even greater fluorescence intensity of the actinotrichia compared to the previously reported visualization line ( Kuroda et al, 2018 ) ( Supplementary Figures 1 , 2 ). Using previously reported methods ( Kuroda et al, 2018 ), we first isolated the actinotrichia and mesenchymal cells from the larval fins of our new transgenic F1 line [5x and1 (2k): And1 full -GFP/5x and1 (MC): Lifeact-mCherry] and cultured them in culture dishes coated with various kinds of substrates.…”
Section: Resultsmentioning
confidence: 39%
“…Previous studies have suggested that actinotrichia are distributed between basal keratinocytes and mesenchymal cells in fins ( Wood and Thorogood, 1987 ; Smith et al, 2008 ; König et al, 2018 ; Kuroda et al, 2018 ). Basal keratinocytes are in contact with the outer part of the two actinotrichia rows whereas mesenchymal cells are in contact with the inner part.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations